Effects of exposure to community violence and family violence on school functioning problems among urban youth: The potential mediating role of posttraumatic stress symptoms - Tia eMcGill; Shannon R Self-Brown; Betty S. Lai; Melissa eCowart; Ashwini eTiwari; Monique eLeBlanc; Mary Lou eKelley (Frontiers Media S.A., 2014)
Adolescents who are exposed to violence during childhood are at an increased risk for developing posttraumatic stress (PTS) symptoms. The literature suggests that violence exposure might also have negative effects on school functioning, and that PTS might serve as a potential mediator in this association. The purpose of the current study was to replicate and extend prior research by examining PTS symptoms as a mediator of the relationship between two types of violence exposure and school functioning problems among adolescent youth from an urban setting. Participants included a sample of 121 junior high and high school students (M= 15 years; range= 13-16 years; 60 males, 61 females) within high-crime neighborhoods. Consistent with our hypotheses, community violence and family violence were associated with PTS symptoms and school functioning problems. Our data suggest that community and family violence were indirectly related to school functioning problems through PTS symptoms. Findings from this study demonstrate that PTS symptoms potentially mediate the relationship between violence exposure and school functioning problems across two settings (community and home). Future research should further examine protective factors that can prevent youth violence exposure as well as negative outcomes related to violence.